2020
DOI: 10.1093/cid/ciaa042
|View full text |Cite
|
Sign up to set email alerts
|

Trachoma, Anti-Pgp3 Serology, and Ocular Chlamydia trachomatis Infection in Papua New Guinea

Abstract: Background In Melanesia, the prevalence of trachomatous inflammation–follicular (TF) suggests that public health–level interventions against active trachoma are needed. However, the prevalence of trachomatous trichiasis is below the threshold for elimination as a public health problem and evidence of conjunctival infection with trachoma’s causative organism (Chlamydia trachomatis [CT]) is rare. Here, we examine the prevalence of ocular infection with CT and previous exposure to CT in three ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
6
1
Order By: Relevance
“…In the Torres Strait, the absence of C. trachomatis by PCR makes other unidentified viral or allergic causes the more likely precipitants for the follicular conjunctivitis consistent with TF found. Our results resemble those reported in the Melanesian nations of PNG, Solomon Islands, and Vanuatu where the prevalence of TF is high in children, but ocular C. trachomatis infection is uncommon and TT is rarely seen in adults 29–32 . Follow‐up surveys in the Solomon Islands found a range of non‐chlamydial pathogens detected in individuals with TF but, as with our study, a single dominant aetiology to explain prevalent TF was unable to be identified 33 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the Torres Strait, the absence of C. trachomatis by PCR makes other unidentified viral or allergic causes the more likely precipitants for the follicular conjunctivitis consistent with TF found. Our results resemble those reported in the Melanesian nations of PNG, Solomon Islands, and Vanuatu where the prevalence of TF is high in children, but ocular C. trachomatis infection is uncommon and TT is rarely seen in adults 29–32 . Follow‐up surveys in the Solomon Islands found a range of non‐chlamydial pathogens detected in individuals with TF but, as with our study, a single dominant aetiology to explain prevalent TF was unable to be identified 33 .…”
Section: Discussionsupporting
confidence: 78%
“…The high prevalence of TF, together with the absence of TI in children and lack of TT in adults, paints a conflicting clinical picture of the public health threat posed by trachoma in this community. The valuable insights gained through laboratory testing and detailed clinical examination performed by an ophthalmologist suggests that trachoma [29][30][31][32] Follow-up surveys in the Solomon Islands found a range of nonchlamydial pathogens detected in individuals with TF but, as with our study, a single dominant aetiology to explain prevalent TF was unable to be identified. 33 Future options for work in the Torres Strait could include using metagenomic deep sequencing for the identification of unexpected pathogens.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Whilst results could not be used as a prevalence estimate for programmatic planning, the findings did suggest that active trachoma may be a public health problem and provided justification for further investigation [ 11 ]. Subsequent population-based surveys in the neighbouring countries of Papua New Guinea (PNG), Solomon Islands, and Vanuatu had similar findings [ 12 15 ]. Additionally, there was little indication in those countries of current C .…”
Section: Introductionmentioning
confidence: 85%
“…trachomatis infection in children, based on polymerase chain reaction (PCR) detection on conjunctival swabs, or past infection based on antibodies to the C . trachomatis antigen Pgp3 [ 12 , 15 17 ]. It was therefore hypothesised that in these three Melanesian nations, as-yet undetermined aetiologies may be responsible for much of the clinical syndrome that is phenotypically indistinguishable from TF, a phenomenon referred to as the “Pacific enigma” [ 16 ].…”
Section: Introductionmentioning
confidence: 99%